2016
DOI: 10.1039/c6ra11390g
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticle-modified TiO2/SBA-15 nanocomposites as active plasmonic photocatalysts for the selective oxidation of aromatic alcohols

Abstract: The catalytic performance of noble-metal on mesoporous silica hosts has been widely investigated because the effects of surface plasmon resonance can open new avenues for the improvement of catalytic performance under light irradiation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 55 publications
1
23
0
Order By: Relevance
“…Selective photooxidation of alcohols has received special attention from research groups in the recent years due to economical feasibility (no heating is applied) and ecofriendliness. A variety of studies dedicated to partial oxidation of aromatic alcohols features titania-based systems with such modifiers (or combination thereof) as CdS [157], ZnO [158], WO 3 [159], CeO 2 [160], Fe 3+ [161], vanadyl species [162], Ag [163], AgBr [164,165], Au [166], Pt, Rh or Ir [167]. A selection of recent works on the subject also mention gold catalysts on different supports such as hydrotalcite [168], niobium oxide perovskites [169], zeolites [170] or CeO 2 [171].…”
Section: Selective Photooxidation Of Alcoholsmentioning
confidence: 99%
“…Selective photooxidation of alcohols has received special attention from research groups in the recent years due to economical feasibility (no heating is applied) and ecofriendliness. A variety of studies dedicated to partial oxidation of aromatic alcohols features titania-based systems with such modifiers (or combination thereof) as CdS [157], ZnO [158], WO 3 [159], CeO 2 [160], Fe 3+ [161], vanadyl species [162], Ag [163], AgBr [164,165], Au [166], Pt, Rh or Ir [167]. A selection of recent works on the subject also mention gold catalysts on different supports such as hydrotalcite [168], niobium oxide perovskites [169], zeolites [170] or CeO 2 [171].…”
Section: Selective Photooxidation Of Alcoholsmentioning
confidence: 99%
“…Hallet-Tapley et al [43] also demonstrated the ability of Au supported on hydrotalcite, ZnO, or Al 2 O 3 to selectively oxidize sec-phenethyl to acetophenone and benzyl alcohol to benzaldehyde, in presence of H 2 O 2 using 530 nm LED as the photoexcitation source ( Figure 4A). Yu et al [44] and more recently, Chen et al [45] supported gold catalysts for the selective aerobic oxidation of benzyl alcohol to benzaldehyde driven by visible light. Plasmonic photocatalysis has also been applied to amide production via tandem oxidation/amidation processes catalyzed by Au/SiO 2 under 532 nm laser irradiation [46].…”
Section: Oxidation Reactionsmentioning
confidence: 99%
“…Similarly, benzyl alcohol and its derivatives can be oxidized to their corresponding benzyl aldehydes via visible light photocatalysis in water as well as several non-aqueous solvents including acetonitrile and toluene. [18][19][20] It has been reported that the selectivity of this reaction is higher in acetonitrile than in water. 21,22 This paper offers a novel and more selective method for the photocatalytic production of DHA from glycerol by using acetonitrile as the reaction medium.…”
Section: Introductionmentioning
confidence: 99%